Smuggling Conspiracies - Mimi Whittaker (Columbia Journal of Race and Law, 2025)
Amid growing political polarization, human trafficking remains one of the few social causes that retains universal bipartisan support. Nowhere was this clearer than Florida in the spring of 2023, when Governor Ron DeSantis passed widely popular human trafficking reforms. Despite a legislative session marked by national controversy over the state’s extreme antiimmigrant proposals that year, DeSantis’ rhetoric on human trafficking specifically called for the protection of immigrant victims. The story behind the 2023 reforms reveals not a benevolent change of heart or momentary hypocrisy, but an ominous call towards racist tropes plaguing human trafficking and immigration reform for centuries. This Article conducts an extensive legislative history and argues that DeSantis’ legislative efforts tap into theories popularized by QAnon, a far-right decentralized web of conspiracies. In doing so, Florida echoes historical racial narratives and utilizes dog whistles to further justify an expansion of its immigration enforcement powers. The strategy behind Florida’s efforts to generate anti-immigrant hysteria has extended to other states and is now being carried out on a national stage under the new Trump administration. This Article contends that advocates must meet this growing threat by crafting multidisciplinary counter-narratives that directly confront the role of race and reject the respectability politics dominating mainstream trafficking discourse.